A Study to Assess the Oral Health Related Quality of Life among Eunuchs Residing in Central Gujarat - Kalyan, Pulkit; Dave, Bhavna; Deshpande, Neeraj; Panchal, Darpan (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: The health and quality of life overall are affected by an individual’s oral health. The low- and middle-income countries are affected by inadequate attention to oral health, which results in oral disease becoming a major public health problem that needs to be addressed. This is the reason, recently, there is increasing attention and global awareness given to oral health and its various determinants. Oral Health-Related Quality of Life (OHRQoL) is defined by individual assessment of several oral health dimensions, including physical dental function, tooth pain, psychological discomfort, and social impacts–all of which affect overall well-being. Self-reported subjective indicators of OHRQoL correlate well with objective clinical measures of oral health status. So OHRQoL at the individual level points to the need for clinical treatment and at the population level can be used to evaluate oral health interventions. Objectives: To assess the OHRQoL using OHIP 14 and to analyze the association between the OHRQoL using OHIP 14 and various demographic variables. Methodology: The survey was conducted among the 384 eunuchs living in central Gujarat. Non-probability snowball sampling was used in the inclusion of self-identified eunuchs. The data was recorded by one examiner (primary investigator) and one recorder (calibrated dental hygienist) for the entire study. The data was collected through structured schedules, resulting in quantitative data. The data was analyzed with the chi-square test of association, the Mann-Whitney U test, and the Kruskal-Wallis test using SPSS version 21. Results: The study shows that out of 384 eunuchs, 1.04% were children less than 11 years old, 3.9% were adolescents, 74.44% were adults who were more than 18 years old and less than 60 years and the remaining sample, that is, 20.5%, were more than 60 years old. 27.5% of the participants had an educational background, 87% of the participants were dentate, and the remaining were edentate. The oral health-related quality of life showed significant association and difference between the various parameters and the demographic variable. Conclusion: In general, the quality of dental health and oral health-related quality of life are interlinked and positively associated with the various demographic factors like gender, age group, educational background, and income. The eunuchs form a vulnerable population, and immediate action is required in preventive and promotive aspects to improve the oral health-related quality of life, which in turn would improve the overall quality of life. This in turn will drive this socially stigmatized community to have a positive dental health attitude and behavior.